Achievement of more stringent disease control is associated with reduced burden on workplace and household productivity: results from long-term certolizumab pegol treatment in patients with psoriatic arthritis. (December 2022) - Tillett, William; Coates, Laura C.; Kiri, Sandeep; Taieb, Vanessa; Willems, Damon; Mease, Philip J.
Background: Psoriatic arthritis (PsA) impacts the physical health and functional ability of patients, leading to reduced productivity. High unemployment rates and absence due to sickness have been reported in patients with PsA. Objectives: This post hoc study investigated certolizumab pegol treatment impact on workplace and household productivity in patients with PsA, and assessed whether achievement of more stringent disease control was associated with greater improvements in productivity. Design: RAPID-PsA was a 216-week phase III trial. Methods: This post hoc study used a generalised estimating equations (GEE) model to examine the disease activity association, measured using American College of Rheumatology (ACR) and Disease Activity in PSoriatic Arthritis (DAPSA), and workplace and household productivity, assessed using an arthritis-specific Work Productivity Survey (WPS). The GEE model estimated the mean cumulative number of days patients meeting different disease control criteria were affected by absenteeism or presenteeism in the workplace and household. Results: In all, 273 patients were randomised to certolizumab pegol and 183 (67.0%) completed Week 216. At baseline, 60.8% of patients were employed outside the home. Improved disease control, measured using ACR and DAPSA criteria, was associated with fewer cumulative days affected by workplace absenteeism through Week 216: ACR70: 4.1 days, ACR50 to <70: 7.7, ACR20 to <50: 20.9, <ACR20: 35.7; DAPSA remission (REM): 3.3, low disease activity (LDA): 9.8, moderate disease activity (MoDA): 22.4, high disease activity (HDA): 54.0. Improved disease control was also associated with fewer days affected by workplace presenteeism: ACR70: 5.6, ACR50 to <70: 19.3, ACR20 to <50: 71.2, < ACR20: 141.2; DAPSA REM: 5.7, LDA: 25.8, MoDA: 77.2, HDA: 223.6. Similar associations between greater disease control and improved productivity were observed for household absenteeism and presenteeism. Conclusion: This post hoc study demonstrates the cumulative workplace and household work productivity benefits for patients with PsA when achieving more stringent thresholds of disease control with certolizumab pegol treatment.